In vitro and in vivo effect of Clinacanthus nutans (Burm. f.) Lindau aqueous extract on IgE and IgG-mediated allergy pathways - Kow, Audrey Siew Foong (2021)
Allergy is a hypersensitive reaction against antigens which could be mediated through immunoglobulin (Ig) -E and IgG. About 30 – 40% of people globally are affected with allergy and it is projected to increase due to urbanisation. It has both personal and economic implications thus, requiring urgent attention. Clinacanthus nutans (Burm. f.) Lindau (C. nutans) is commonly found in Malaysia, Thailand and Indonesia. Traditionally used to treat snake and insect bites, skin rashes and others, it was evaluated for its anti-viral, antiinflammatory and anti-cancer properties. Although used to treat skin rashes, its anti-allergy property was not evaluated. Hence, this study evaluated the antiallergy property of C. nutans in in vitro and in vivo allergy models and its underlying mechanism. Meta-analysis was done to identify the commonly analysed soluble mediators in the less established IgG pathway (compared to IgE). The anti-allergy property via IgE pathway of 100% ethanolic, 70% ethanolic-aqueous, 50% ethanolic-aqueous and aqueous C. nutans extracts was assessed through in vitro IgE-induced mast cell degranulation model. The most active extract was then evaluated in IgG-induced macrophage activation model. The underlying mechanism was studied by analysing its effect on the mitogen-activated protein kinase (MAPK) and phosphoinositide-3-kinase (PI3K) pathways’ proteins by Western blotting. The effect was then validated in rodents. Acute toxicity test that analysed the haematological, biochemical and histological profiles was done to determine its safety and safe doses to be used. The overall effect was analysed in ovalbumin-challenged active systemic anaphylaxis (OVA-ASA), whereby both IgE and IgG pathways were activated. The effect of CNAE on specific targeted pathway was analysed in IgE challenged passive systemic anaphylaxis (IgE-PSA) and IgG-PSA models. Soluble mediators were quantified by enzyme-linked immunosorbent assay (ELISA). The commonly studied soluble mediators of IgG pathway identified through meta-analysis were platelet activating factor (PAF), histamine, interleukins (IL)-6, -13 and tumour necrosis factor-α (TNF-α). The most active extract - CNAE significantly reduced histamine and β-hexosaminidase in IgE induced mast cell degranulation model at 5 mg/mL and above. In the IgG induced macrophage activation model, significant decrease of IL-6 and TNF-α were recorded at 1.75 mg/mL and this was due to the inhibition of the phosphorylation of ERK1/2 of the MAPK pathway. From the acute toxicity test, 5000 mg/kg of CNAE (single dose) was not toxic to the animals and the doses - 125, 500 and 2000 mg/kg were chosen for subsequent analyses. In OVA-ASA, CNAE (2000 mg/kg) inhibited IgG (89.5%), PAF (171.1%) and IL-6 (92.6%) but not IgE. There was no significant inhibition of histamine, IL-4 and leukotriene C4 (LTC4) in IgE-PSA even at 2000 mg/kg. However, at 2000 mg/kg, there was 128.2% reduction of PAF and 124.4% reduction of IL-6 in IgG-PSA. Significant reduction of histamine in in vitro IgE-induced mast cell degranulation that was not recorded in IgE-PSA could be due to the overall effect of different cells that were activated in IgE-PSA. In the in vitro model, Rat Basophilic Leukaemic (RBL-2H3) cells which mimicked mast cells were specifically induced while in IgE-PSA, other cells with high-affinity IgE receptor (FcεRI) such as mast cells, eosinophils and basophils were challenged giving an overall effect. In conclusion, the anti-allergy property of C. nutans was potentially in CNAE which targeted the IgG pathway with significant reductions of PAF, IL-6 and TNF-α by inhibiting ERK1/2 pathway. As anaphylaxis is a systemic allergy, the anti-allergy effect of CNAE could be further evaluated on localised models such as atopic eczema or allergic alveolitis.